2018
DOI: 10.32568/jfce.403131
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Questionnaire on Online Gaming Addiction for University Students

Abstract: The study is aimed to adapt the Online Gaming Addiction Questionnaire for university students. The research sample consists of 254 university students receiving education in Sakarya and İzmir provinces and playing online games. Three subscales, explaining 63.1% of the total variance, were obtained in compliance with the original scale via factor analysis. The analysis for criterion validity showed that, there is 59.7% positive correlation between the present research and that of Young's Questionnaire on Intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…When it was evaluated in terms of gender, it was observed that the male students played online games more frequently than their female counterparts and differed from them. This finding was similar to the ones mentioned in the literature (Bekir and Yıldırım, 2018;Bekir and Çelik, 2019;Bekir, 2018;Ko et al, 2005;McInroy and Mishna, 2017). It was also found that playing Internet games was positively correlated with aggressiveness (Kim et al, 2008;Mehroof and Griffiths, 2010), but it was negatively correlated with controlling oneself (Kim et al, 2008).…”
Section: Found Insupporting
confidence: 90%
See 1 more Smart Citation
“…When it was evaluated in terms of gender, it was observed that the male students played online games more frequently than their female counterparts and differed from them. This finding was similar to the ones mentioned in the literature (Bekir and Yıldırım, 2018;Bekir and Çelik, 2019;Bekir, 2018;Ko et al, 2005;McInroy and Mishna, 2017). It was also found that playing Internet games was positively correlated with aggressiveness (Kim et al, 2008;Mehroof and Griffiths, 2010), but it was negatively correlated with controlling oneself (Kim et al, 2008).…”
Section: Found Insupporting
confidence: 90%
“…It was also found that playing Internet games was positively correlated with aggressiveness (Kim et al, 2008;Mehroof and Griffiths, 2010), but it was negatively correlated with controlling oneself (Kim et al, 2008). Studies in Turkey also give similar results (Bekir and Yıldırım, 2018;Mustafaoğlu and Yasacı, 2018).…”
Section: Found Inmentioning
confidence: 66%
“…As a result of the literature review, it can be thought that online gaming addiction will have a negative impact on people, and that it will affect the students, which constitute an important part of the society, in terms of cognitive, emotional and social aspects. However, there is a limited number of studies in the literature related to online gaming addiction that has recently been identified as an addiction type (Bekir & Çelik, 2019;Bekir & Yıldırım, 2018;Kaya, 2013;Mehroof & Griffiths, 2010;Young, 2009;Ng & Wiemer-Hastings, 2005). Nonetheless, when these researches were examined, it becomes evident that no research that examined the relationship between emotional schemas and agentic personality and online game addiction in the university sample was found.…”
Section: Wwwmojetnetmentioning
confidence: 99%
“…The data of online game addiction level was collected through Online Game Addiction Scale (OGAS) which was developed by Kaya (2013) for high school students and then later used for university students by Bekir and Yıldırım (2018). OGAS is a measurement tool consisting of fivepoint Likert questionnaire (1= strongly disagree, 2= disagree, 3= neutral, 4= agree, 5= strongly agree) and three sub-dimensions (i.e.…”
Section: Online Game Addiction Scale (Ogas)mentioning
confidence: 99%
“…It has been recently observed that Internet-based activities such as gaming or chatting exhibit addiction on a similar level to drug and substance abuse. As Internet has become more available via smartphones today, the relationship between smartphone and addiction is now one of the important issues to be addressed (Bekir & Yıldırım, 2018;Kwon, Kim, Cho, & Yang, 2013;Padır, 2016). Şar, Ayas, & Horzum (2015) state that excessive and unconscious usage of smartphone may cause behavioral addiction as well.…”
Section: Introductionmentioning
confidence: 99%